Toda and Volterra lattice equations from discrete symmetries of KP hierarchies - Aratyn, H.; Ferreira, L. A. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP] (Elsevier, 1993)
The discrete models of the Toda and Volterra chains are being constructed out of the continuum two-boson KP hierarchies. The main tool is the discrete symmetry preserving the Hamiltonian structure of the continuum models. The two-boson currents of KP hierarchy are being associated with sites of the corresponding chain by successive actions of discrete symmetry.